Monitoring System for Circular Deformation in Metro Shield Tunnels in Soft Soils - Jinfeng Zhang; Ming Zhao (Advances in Civil Engineering)
For in-service metro shield tunnels in soft soils, large circular deformations are a major concern because they usually lead to various problems, such as water leakage, joint openings, and concrete cracks. However, the monitoring of circular deformation depends mainly on manual surveying, and the automatic monitoring methods developed in recent years generally have low economic applicability and are not widely implemented. In this study, an automatic and cost-effective system was presented to monitor circular deformation in shield tunnels by using only inclinometers. Experiments were conducted to prove the assumption that each segment can be regarded as a rigid body and to investigate the position of the joint rotation center. Then, a method for monitoring circular deformation based on the rigid body and plane section assumptions was proposed. The joint opening angle, maximum joint opening width, horizontal diameter convergence, and bolt strain were calculated from rotation angles of segments which can be monitored directly by inclinometer. A case study was conducted for a section of a metro shield tunnel with an ongoing pit excavation nearby. The rotation of segments was measured using MEMS inclinometers, and the data were transmitted using ZigBee and general packet radio service (GPRS) wireless communication technology. Results show that the proposed system could be implemented to improve transportation safety in relevant situations and similar conditions.